AN EFFICIENT WATERMARKING SCHEME FOR H.264/AVC COMPRESSED VIDEO - Dawen Xu (ICTACT Journal on Image and Video Processing, 2014)
Since H.264/AVC is the most widely-deployed video coding standard and has gained dominance, the necessity of copyright protection and authentication that are appropriate for this standard is unquestionable. According to H.264/AVC specific codec architecture, an efficient watermarking scheme for H.264/AVC video is proposed. The watermark information is embedded into quantized residual coefficients by slightly modulating the coefficients with specific symbol encoding, instead of directly adding the watermark to the quantized coefficients. It is not necessary to fully decode H.264/AVC compressed stream both in the embedding and extracting processes. Experimental results show that the proposed scheme can preserve high imperceptibility while achieving enough robustness against various attacks such as requantization, transcoding, AWGN, brightness and contrast adjustment.